The Lesson Plan Analysis on Learning Activities in Writing at the Tenth Grade of SMK Negeri 2 Alasa Talumuzoi - Carolina Gulo, Irene; Tahir Harefa, Afore; Piarawan Zebua, Elwin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This qualitative study aims to understand the process of designing lesson plans for writing activities in the tenth grade at SMK Negeri 2 Alasa Talumuzoi for the academic year 2022/2023 and identify challenges faced by an English teacher during implementation. Data was collected through observations and interviews with the teacher. The analysis followed qualitative techniques, leading to conclusions based on the research objectives. The findings reveal that the teacher's lesson planning process includes various components such as educational details, competencies, objectives, materials, methods, activities, and assessments. The teacher effectively designs the lesson plan. However, challenges were identified, including incomplete alignment between competencies and activities, lack of clear instructions for students, underutilization of teaching media, inadequate final assessments, and limited student involvement in summarization. This research provides insights into the strengths and weaknesses of lesson planning and implementation in the context of writing activities.